P224 How do the timings of reactions during specific inhalation challenge relate to real world exposures in occupational asthma?. (15th November 2017) - Moore, VC; Burge, PS; Robertson, AS; Walters, GI
Abstract : Timings of asthmatic reactions following specific inhalation challenge (SIC) have been defined as immediate, late, dual and prolonged immediate. How they translate into usual workplaces exposure is unknown. We postulated that those with an immediate component would start to react within one hour of regular occupational exposure and start to recover within one hour of leaving work, whereas those with a late reaction would have delayed starting and recovery. Those with dual or prolonged immediate reactions would show early deterioration and delayed recovery. We have compared the timings of reactions in 48 consecutive workers who had positive SIC and had kept serial PEF records at home and with real-world work exposures. These were analysed by the ABC plot from the Oasys analytical program which combines all measurements done on different work days into 2-hourly blocks and produces plots similar to that seen with SIC, with days away from work as the control exposure. Four experts independently scored the ABC plots to identify workplace deterioration starting at the first timepoint after the start of work, or ≥2 hours later (delayed deterioration), and starting to recover at the first timepoint after leaving work, or ≥2 hours later (delayed recovery). Records with disagreements were resolved in a joint meeting when all records available for an individual worker were compared. The relationship between SIC and real-world exposures is shown in the table . The relationship between laboratory and workplace reactions was only modest, complete concordance in 44%. Exposures may vary from day to day at work, or that the first reading at work was made before significant exposure has occurred; workers are instructed to make the last reading before work immediate before entering the workplace which should mitigate this. For those with immediate reactions alone during SIC, more showed deterioration in the first workplace reading than showed early recovery after leaving work.